Show and Tell Techniques dalam Meningkatkan Kemampuan Public Speaking Siswa MA Ulul Albab Makassar - Rijal, Andi Samsu; Sulviana, Sulviana; Mursidin, Muthmainnah; Jusmaniar, Jusmaniar; Imran, Muhammad Chairil; Nurjannah, Sitti; Indahyanti, Rizka; Mujahidah, Mujahidah (Ash-Shahabah : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aimed to improve the public speaking skills of MA Ulul Albab Makassar students. The activity method applied was a participatory method, in the sense that the implementation of the activity emphasizes active student participation, involving teachers and stakeholders at school. The activity was carried out in February 2025 with several stages, including; observation, participant recruitment activities, implementation stages, public speaking practice and evaluation. The output of this activity has a significant impact on improving students' public speaking both in terms of hard skills and soft skills. Students' hard skill abilities were seen from students' verbal abilities, stage mastery, and interactive aspects to the audience. Improvement in soft skills was measured from the aspect of material that has Pancasila character content and local wisdom values ​​of the Bugis-Makassar community, as well as aspects of students' attitudes and behavior both in and outside the classroom.